Nitrogen fertilization in wheat: influence on yield and water use efficiency. Semi-arid Pampas Region. (Semiárida, 2020)
During wheat season 1985/6 the fertilization influence was studied at sowing (100 kg N/ha applied in early growing = CT) and a combined fertilization (30 kg N/ha in early growing + 70 kg/ha - in hearing) on both. a modern wheat cultivar (Buck Pucará) and a traditional one (Buck Napostá). In both cultivars. the fertilization treatments increased yields significantly (greater number of heads per unit area grain per ear and 1000 seeds weight). The traditional cultivar did not show significant differences in water consumption under fertilization treatments. However, fertilization increased the efficiency of water consumption (tester = 1.77; CT = 4.25 and CT+E = 3.85 kg/ha mm).